Review of Tuberous Sclerosis Complex: A Single Center Experience - Ayşe Tosun; Beste Kıpçak Yüzbaşı; Ali Akyol (Journal of Pediatric Research)

(untitled)
Aim:The aim of this study is to review the clinical features and treatment of tuberous sclerosis complex patients followed up in our hospital and to compare our findings with the literature.Materials and Methods:The clinical-laboratory findings and treatment of 15 tuberous sclerosis patients who presented at a child neurology policlinic between 2007-2017 were retrospectively reviewed.Results:Fifteen patients aged between 8 months and 17 years were included in the study. The female/male ratio was 47%/53%. Thirteen patients (86%) were referred with convulsions, 1 (7%) with skin hypo-pigmented macule and 1 (7%) with the detection of a renal cyst in ultrasonography. At the time of diagnosis, skin findings were present in 93% of the patients. There were infantile spasms in 23%, focal seizures in 54%, generalized tonic-clonic in 15% and atonic seizures in 8% of those patients who referred with seizures. In addition to the known antiepileptics in treatment, mTOR inhibitors were used in two patients. Forty percent were diagnosed with resistant epilepsy. Seven of the patients (46%) had various levels of mental retardation. There were cardiac findings in 33%, ocular findings in 33%, and renal involvement in 27% of the patients. The most common (87%) neuroradiologic finding was subependymal nodule.Conclusion:It was observed that the signs and symptoms of our patients were compatible with the literature. In childhood, refractory epilepsy and mental retardation were the most important clinical findings. The age of onset of seizures in patients with resistant epilepsy was under one year of age. These patients had infantile spasms and a larger number of cortical tubers in cranial magnetic resonance imaging findings. It was observed that everolimus treatment had no marked effect on seizure frequency. However, patients with tuberous sclerosis should be closely monitored for the development of malignancies in the long term and this monitoring should be continued in adulthood.